Personal Pronoun Ngana and its Use in Manado Malay Sentence - Mandang, Ferry Hertog (Soegijapranata Catholic University, 2021)
The implementation of ngana as one of the personal pronouns is found in Manado Malay language. The word ngana is often used in sentences by Manado Malay speakers. Usually, the use of the word ngana used by parents for younger people, close friends, and peers. The purpose of this study is to describe the word ngana in the sentence, the word ngana as subject in the sentence, and the word ngana as function in the sentence. This research used distributional method and the technique used is substitution or replacement, namely by replacing other units or certain elements of morphological constructs or logical phrases by other elements. The results showed that ngana in sentences can be seen from interlocutors, age, closeness, socioeconomic, education and position. Ngana can be placed in front of the subject and also behind the subject of the sentence. In terms of syntactic function, ngana occupies the function of the subject in active sentence.